Pengaruh Kecepatan Terhadap Kemampuan Menggiring Bola Pada Siswa Yang Mengikuti Ekstrkulikuler Sepak Bola Di Sd Negeri 112322 Padang Nabidang - Daulae, Ervin Mangaraja; Sari, Liliana Puspa (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2025)
Students at SD Negeri 112322 Padang Nafeld don't really understand that by practicing these basic techniques they can have an influence in a soccer game. The aim of this research was to determine the influence of speed, flexibility and agility on the ability to dribble the ball at SD Negeri 112322 Padang Nafeld. This research is correlation research, namely research that aims to investigate the extent to which variations in one variable are related to variations in one or more other variables based on the correlation coefficient. The instruments in this research were speed measurement tests and ball dribbling. The research subjects used were 30 students at SD Negeri 112322 Padang Nafeld who took part in soccer extracurricular activities. Data analysis techniques used to test the hypothesis of prochict moment correlation analysis at a significance level of 5%